The reformation of faith in the context of late medieval theology and piety : essays by Berndt Hamm - Hamm, Berndt (Brill, 2004)
Annotation This book comprises the first major collection of articles in English translation by University of Erlangen Professor Dr. Berndt Hamm, one of the most important and innovative scholars of the intellectual history of late-medieval and Reformation Germany. The articles herein trace the evolution of Christian theology and piety from the twelfth through the sixteenth centuries, employing a variety of disciplines and interpretative models to chart transformations with extraordinary attention to historical context. Hamm's intensive work with previously unknown sermon collections, devotional works, and pastoral care manuals from the later middle ages serves as the basis for a new appraisal of the lines of continuity and change between that era and the German Reformation.
Keywords: Reformation.; Theology, Doctrinal -- History -- Middle Ages, 600-1500.; Christian life -- History -- Middle Ages, 600-1500.; Church history -- Middle Ages, 600-1500.; Réforme (Christianisme); Théologie dogmatique -- Histoire -- 600-1500 (Moyen Âge); Vie chrétienne -- Histoire -- 600-1500 (Moyen Âge); Église -- Histoire -- 600-1500 (Moyen Âge); RELIGION -- Christian Church -- History.; RELIGION -- Christianity -- History.; Christian life -- Middle Ages; Church history -- Middle Ages; Reformation; Theology, Doctrinal -- Middle Ages; Christendom.; Reformatie.; 600-1500; History